Particulate matter 10 exposure affects intestinal functionality in both inflamed 2D intestinal epithelial cell and 3D intestinal organoid models - Son, Ye Seul; Son, Naeun; Yu, Won Dong; Baek, Aruem; Park, Young-Jun; Lee, Moo-Seung; Lee, Seon-Jin; Kim, Dae-Soo; Son, Mi-Young (Frontiers in Immunology, 2023)
A growing body of evidence suggests that particulate matter (PM10) enters the gastrointestinal (GI) tract directly, causing the GI epithelial cells to function less efficiently, leading to inflammation and an imbalance in the gut microbiome. PM10 may, however, act as an exacerbation factor in patients with inflamed intestinal epithelium, which is associated with inflammatory bowel disease. In this study, we established chronically inflamed intestinal epithelium models utilizing two-dimensional (2D) human intestinal epithelial cells (hIECs) and 3D human intestinal organoids (hIOs), which mimic in vivo cellular diversity and function, in order to examine the deleterious effects of PM10 in human intestine-like in vitro models. Inflamed 2D hIECs and 3D hIOs exhibited pathological features, such as inflammation, decreased intestinal markers, and defective epithelial barrier function. In addition, we found that PM10 exposure induced a more severe disturbance of peptide uptake in inflamed 2D hIECs and 3D hIOs than in control cells. This was due to the fact that it interferes with calcium signaling, protein digestion, and absorption pathways. The findings demonstrate that PM10-induced epithelial alterations contribute to the exacerbation of inflammatory disorders caused by the intestine. According to our findings, 2D hIEC and 3D hIO models could be powerful in vitro platforms for the evaluation of the causal relationship between PM exposure and abnormal human intestinal functions.